Quantitative study of phosphate phophorus fluctuation in the freshwater fishpond of the UP college of fisheries. - Fortes, Romeo D. (College of Fisheries, University of the Philippines, 1968)
The effect of weather conditions and rainfall, on the phosphate-phosphorus fluctuation in the freshwater fishpond of the U.P College of Fisheries was studied. Other factors such as temperature, fertilization, dilution and phytoplankton population were considered. It appears that, when light intensity is high at one time, decline of phosphate concentration follow; when the amount of rainfall is high, sooner or later, phytoplankton is increased. It is also apparent that in general, phytoplankton population has an inverse relation to phosphate concentration while fertilization directly increases it. Dilution either from the rain or from the fire hydrant caused a decrease of phosphate content temporarily but after a certain period of time the amount of phosphate slightly increased.